Differential Chaos Shift Keying for FSO Systems: A Novel Approach Under Turbulence and Boresight Pointing Errors - Gyan Deep Verma; Aashish Mathur; Manav R. Bhatnagar (IEEE Open Journal of the Communications Society)
In the last two decades, chaos-based signals have achieved much popularity due to their useful waveform properties such as non-periodicity, wide-band nature, and robustness against eavesdropping by intruders. In this paper, we utilize differential chaos shift keying (DCSK) for free space optical (FSO) communication systems to improve their performance under the combined influence of atmospheric turbulence (AT) and non-zero boresight pointing errors (PEs). We employ the generalized Malaga distribution for modeling the channel gain under all turbulence regimes from weak to strong. Moreover, we utilize the modified Rayleigh distribution to incorporate the effect of jitter and boresight PEs. The computation of the exact average bit error rate (ABER) expression for the proposed FSO system using DCSK is quite tedious. Therefore, we propose two approximations for ABER of the proposed system which show a tight match with the exact analysis and are also valid for the homodyne detection (HMD), heterodyne detection (HD), and intensity modulation/direct detection (IM/DD) techniques. We also observe the impact of different AT parameters $(α,β)$ , spreading factor $(M)$ , and non-zero boresight PE parameters $(k_{x},k_{y})$ on the ABER performance of the DCSK-based FSO system. Further, we derive asymptotic ABER expression to obtain insightful observations into the FSO system performance. We also compare the ABER performance of the proposed DCSK-based FSO system with an FSO system employing, correlation delay shift keying (CDSK), binary phase shift keying (BPSK), and code division multiple access (CDMA). We also derive the generalized ergodic capacity (EC) for the considered FSO communication system and show the effect of the spreading factor and boresight on the EC of the DCSK FSO communication system. We derive closed form expression of the average secrecy capacity (ASC) under the combined effect of AT and nonzero boresight PEs for the considered DCSK FSO system.